(untitled) (Proceedings of International Conference on Special Education, 2025)
Inclusive Inclusive mathematics teaching aims to integrate students with special educational needs (SEN) and mainstream learners in the same classroom to ensure equitable access to education. Despite policy efforts in Malaysia through the Inclusive Education Programme (IEP), many Mathematics teachers still face significant challenges in catering to diverse student needs. This study employed a qualitative case study approach involving semi-structured interviews with ten primary school Mathematics teachers experienced in inclusive classrooms. Data were analysed using thematic analysis, guided by the Community of Inquiry (coi) framework, and validated through coder triangulation and member checking. The study identified five key challenges: managing diverse learning abilities, lack of pedagogical knowledge and inclusive resources, time constraints due to syllabus pressure, behavioural disruptions, and limited collaboration with support staff. These issues reveal gaps in professional preparedness and systemic support for inclusive practices. The findings highlight the urgent need for targeted teacher training, collaborative teaching models, and inclusive pedagogical strategies to ensure effective implementation. Embedding inclusive teaching within the coi framework can enhance teaching, cognitive, and social presence in classrooms. This study contributes to understanding the real-world challenges of inclusive mathematics teaching and calls for the development of a competency-based framework to support inclusive practices in Malaysian primary schools.